Treatment of Central Nervous System Infection Caused by Multidrug-Resistant Acinetobacter baumannii with Intravenous and Intraventricular Colistin Sulfate: A Case Report and Literature Review - Yang X; Guo C; Wu G; Zhao K; Xiang D; Xu D; Liu D; He Y (Infection and Drug Resistance, 2023)
Xueping Yang,1,2,* Changhong Guo,3,* Guangjie Wu,1,* Kai Zhao,4 Dong Xiang,1 Dong Xu,5 Dong Liu,1 Yan He1 1Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 2Department of Pharmacy, Jingzhou Hospital of Traditional Chinese Medicine, Jingzhou, 434000, People’s Republic of China; 3Department of Scientific Education, Jingzhou Hospital of Traditional Chinese Medicine, Jingzhou, 434000, People’s Republic of China; 4Department of Neurosurgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China; 5Department of Infection Disease, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan He; Dong Liu, Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China, Email heyan_may@hotmail.com; ld2069@outlook.comPurpose: Due to the spread of antimicrobial-resistant bacteria and poor penetration of many antimicrobial drugs across the blood–brain barrier following intravenous administration, treatment of central nervous system (CNS) infections is challenging, especially infections caused by carbapenem-resistant organisms (CRO). Intraventricular (IVT) infusion of antimicrobial drugs could be a choice. This report aims to describe a patient with CNS infection caused by carbapenem-resistant Acinetobacter baumannii (CRAB) which was successfully treated with IVT combined with intravenous (IV) colistin sulfate.Methods: A case of CNS infection caused by CRAB after a craniocerebral injury was presented. The patient was treated with IVT together with IV colistin sulfate. Moreover, literature on the regimens and safety of colistin sulfate were also reviewed and summarized.Results: Intraventricular (50,000 U, qd/100,000 U, qd) combined with IV (500,000 U, q12h/500,000 U, q8h) colistin sulfate was given to the patient, and the CNS infection was successfully controlled. The patient was finally transferred back to a local hospital for rehabilitation treatment. No nephrotoxicity or neurotoxicity was observed during the therapy.Conclusion: IV combined with IVT colistin sulfate is effective in the treatment of CNS infections caused by CRAB. IVT concomitant IV colistin sulfate might be a therapeutic option worth considering in the treatment of CNS infections caused by CRO.Keywords: central nervous system infection, Acinetobacter baumannii, intraventricular administration, colistin sulfate, colistin, polymyxin